Omentin-1 Levels in Obesity - Putri Hidayasyah Purnama Lestari; Nurahmi Nurahmi; Tenri Esa; Liong Boy Kurniawan (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2021)
Omentin-1 is an anti-inflammatory adipokine secreted by stromal vascular cells. Inflammation and apoptosis of adipocyte tissue in obesity lead to decreased production of omentin-1. This study aims to find the difference in omentin-1 levels in the obese and non-obese groups and the correlation between levels of omentin-1 with BMI and waist circumference. This study was a cross-sectional study involving 70 subjects with 37 people in the obese group and 33 people in the non-obese group. Anthropometric data including weight, height, waist circumference, and BMI were measured. Serum omentin-1 levels were measured by ELISA. The statistical tests used were Chi-square, T-test, Mann-Whitney test, and Spearman test. Test results were significant if p-value < 0.05. Significant difference was observed in serum omentin-1 levels between obese and non-obese group (median 140,31 range (88.08 – 382.76) vs. 210,97 range (124,44–577,96) ng/mL), respectively; p < 0.001). Serum omentin-1 correlated negatively with BMI (p=0.001, r = - 0.398) and waist circumference (p=0.017, r = - 0.286). Obesity causes inflammation and increased death of adipocyte tissues due to apoptosis, autophagy, and fibrosis resulting in decreased production of omentin-1 by stromal vascular cells. Anthropometric parameters of waist circumference and BMI describe the distribution of adipocyte tissue and affect the secretion of omentin-1. Omentin-1 levels in the obese group were lower than in the non-obese group. The higher the BMI and waist circumference, the lower the omentin-1 level.